Differential Expression and Function of PDE8 and PDE4 in Effector T cells: Implications for PDE8 as a Drug Target in Inflammation - Vang, Amanda G.; Basole, Chaitali; Dong, Hongli; Nguyen, Rebecca K.; Housley, William; Guernsey, Linda; Adami, Alexander J.; Thrall, Roger S.; Clark, Robert B.; Epstein, Paul M.; Brocke, Stefan (Frontiers in Pharmacology, 2016)
Abolishing the inhibitory signal of intracellular cAMP is a prerequisite for effector T (Teff) cell function. The regulation of cAMP within leukocytes critically depends on its degradation by cyclic nucleotide phosphodiesterases (PDEs). We have previously shown that PDE8A, a PDE isoform with 40-100-fold greater affinity for cAMP than PDE4, is selectively expressed in Teff versus regulatory T (Treg) cells and controls CD4+ Teff cell adhesion and chemotaxis. Here, we determined PDE8A expression and function in CD4+ Teff cell populations in vivo. Using magnetic bead separation to purify leukocyte populations from the lung draining hilar lymph node (HLN) in a mouse model of ovalbumin-induced allergic airway disease (AAD), we found by Western immunoblot and quantitative (q)RT-PCR that PDE8A protein and gene expression are enhanced in the CD4+ T cell fraction over the course of the acute inflammatory disease and recede at the late tolerant non-inflammatory stage. To evaluate PDE8A as a potential drug target, we compared the selective and combined effects of the recently characterized highly potent PDE8-selective inhibitor PF-04957325 with the PDE4-selective inhibitor piclamilast (PICL). As previously shown, PF-04957325 suppresses T cell adhesion to endothelial cells. In contrast, we found that PICL alone increased firm T cell adhesion to endothelial cells by approximately 20% and significantly abrogated the inhibitory effect of PF-04957325 on T cell adhesion by over 50% when cells were co-exposed to PICL and PF-04957325. Despite its robust effect on T cell adhesion, PF-04957325 was over two orders of magnitude less efficient than PICL in suppressing polyclonal Teff cell proliferation, and showed no effect on cytokine gene expression in these cells. More importantly, PDE8 inhibition did not suppress proliferation and cytokine production of myelin-antigen reactive proinflammatory Teff cells in vivo and in vitro. Thus, targeting PDE8 through PF-04957325 selectively regulates Teff cell interactions with endothelial cells without marked immunosuppression of proliferation, while PDE4 inhibition has partially opposing effects. Collectively, our data identify PF-04957325 as a novel function-specific tool for the suppression of Teff cell adhesion and indicate that PDE4 and PDE8 play unique and non-redundant roles in the control of Teff cell functions.